2007
DOI: 10.1002/pros.20655
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of global gene expression in the bone marrow microenvironment by androgen: Androgen ablation increases insulin‐like growth factor binding protein‐5 expression

Abstract: Androgen suppressive therapy increases IGFBP5 in the BM microenvironment and thereby may facilitate the progression of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…In this instance, the cooperation between c-Src and STAT3 could delay osteoblast differentiation with a positive feedback between IL-6 and c-Src pathways. Consistent with our model, we demonstrated that IL-6 enhances the expression of Igfbp5, which has been described to have important roles in bone physiology and pathology [19][20][21][22] . Interestingly, we found that IGFBP5 directly induced c-Src activation without affecting IGF-1 receptor phosphorylation.…”
Section: Discussionsupporting
confidence: 89%
“…In this instance, the cooperation between c-Src and STAT3 could delay osteoblast differentiation with a positive feedback between IL-6 and c-Src pathways. Consistent with our model, we demonstrated that IL-6 enhances the expression of Igfbp5, which has been described to have important roles in bone physiology and pathology [19][20][21][22] . Interestingly, we found that IGFBP5 directly induced c-Src activation without affecting IGF-1 receptor phosphorylation.…”
Section: Discussionsupporting
confidence: 89%
“…Bcl-2 is an anti-apoptotic protein and its overexpression has been strongly implicated in the development of castration-resistant PCa (McDonell et al , 1992). IGFBP-5 mRNA and protein are upregulated in response to castration and exogenous IGFBP-5 stimulates the proliferation of immortalized prostate epithelial cells (Xu et al , 2007). Also, overexpression of IGFBP-5 accelerates the proliferation of LNCaP cells in androgen-deprived conditions in a PI3K-dependent manner (Miyake et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, insulin-like growth factor-binding protein 5 (IGFBP5) has been shown to induce apoptosis and inhibit tumor growth in breast cancer and osteosarcoma cells (44,45). In contrast, IGFBP5 was found to facilitate the progression of prostate cancer (46). Nevertheless, the reasons for the contradicting functions of IRX1 in different tissue contexts are unclear.…”
Section: Nf-κb Pathway Activation Is Involved In Irx1/cxcl14-induced mentioning
confidence: 99%